Congenital lobar hyperinflation (CHL): A case report with early and differential diagnosis in Neonatal Respiratory Syndrome (Research, Society and Development, 2025)
Congenital lobar hyperinflation (CHL) is a rare lung malformation with a prevalence of 1 in 20,000 to 30,000 births. This is a descriptive study of a clinical case based on data collection during patient follow-up, review of medical records and photographic records. This study aims to elucidate several aspects of CHL, from its diagnosis to prognosis, as a differential diagnosis in Neonatal Respiratory Syndrome. The study describes a clinical case of a newborn who presented respiratory distress in the first hours of life and was diagnosed with CHL. This study highlights the importance of early diagnosis of CHL, where neonatal respiratory failure can be confused with viral infection. Knowledge of this malformation is essential to avoid complications and ensure adequate treatment.